SOCIODEMOGRAPHIC AND CLINICAL PROFILE OF PEOPLE WITH A STOMA DUE TO ONCOLOGICAL CAUSE: OBSERVATIONAL STUDY (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Introduction: Cancer is caused by abnormal cell mutations. Colon and rectum cancer occupies the second position in the ranking of incidences in Brazil. Objective: To describe the sociodemographic and clinical profile of people with an ostomy due to cancer in the state of Ceará. Method: Epidemiological, observational, longitudinal study with a retrospective approach, carried out in Ceará, in medical records of patients monitored by the Service of Attention to the Patient with Stoma. Result: A total of 655 medical records were analyzed, in which most of the patients were female (53%), elderly (61.41%), retired and pensioner (46.9%), married (42%), with children (67.9%), whose predominant schooling was elementary school (34.2%); 72.8% had no comorbidities, did not use chemotherapy (54.5%), colostomy (64.7%), terminal (65.3%), definitive (46%), in the lower left quadrant (52.5%) , red (64.4%), oval (47.2%), low profile (44.6%) and pasty (33.9%), used a one-piece bag (60.6%), with an average of 10 bags monthly (95%), changing every 3 to 5 days (43.1%), without the need to use adjuvants (71%). Conclusion: A profile of patients should be drawn in order to improve assistance and planning of actions for this public.